The role of electronic human resource practices in the sustainable human resource management - Fadhil, Hasan; Al Husseini, Amer (Journal of Management and Business Education, 2023)
Through a theoretical framework, this study aimed to identify definitions of sustainable human resource management by covering the definitions proposed by many researchers and attempting to reach a new definition. Many previous studies have identified many benefits that can be achieved by using sustainable human resource management in organizations. In addition, this study summarized these benefits and identified the most frequently mentioned benefits by reviewing previous studies. The study measured the impact of Electronic -Human Resource practices on Sustainable Human Resource Management in the Iraqi Ministry of Higher Education and Scientific Research by serving 180 employees. The partial least squares (PLS) method in the Smart PLS statistical program (version 4.0.8.9) was used as a statistical method for data analysis. The results of the study showed a relatively acceptable effect of e-human resource practices on sustainable human resource management in the Ministry of Higher Education and Scientific Research. The most important recommendation of this study was that if the Ministry wants to encourage the adoption of new working methods such as sustainable human resource management, it should introduce digital technologies such as artificial intelligence and machine learning in the continuous development and training of employees.